STUDI PENJERNIHAN MINYAK GORENG BEKAS DENGAN METODE PENJERAPAN MENGGUNAKAN BENTONIT MESOPORI DAN ZEOLIT MESOPORI - Alimano, Marsen
This research demonstrates that by reducing particle size lower than 2 ?m could produce mesoporous classified pore diameter (2 – 50 nm). Bentonite and zeolite mesoporous performance test as adsorbent to improve the reusable quality of used cooking oil has been conducted by batch method. This research is intended to accurately ascertain the most influencing parameter for adsorptions process to selected variable by batch concept. Times variance are determined in 40, 55, and 70 minutes by absorbent dosage as main variable are 5, 15, and 25%. Mixing velocity as essential parameter for ultimate adhesion level is determined for 225 and 450 rpm. The result shows that mesoporous bentonite and zeolite adsorptions capability to produce high-quality used cooking oil for color parameter has obtained in 70 minutes process time, absorbent dosage 25% m/m and mixing velocity 450 rpm. The organic values are 97.59 ppm for bentonite (35.42% efficiency) and 95.56 ppm (36.10% efficiency) for zeolite in fresh cooking oil concentrate at 0.0000 Abs (90.477 ppm) and used cooking oil at 0.0997 Abs (151.11 ppm) measured in spectrophotometer wavelength at 489.2 nm. In addition, experiment result obtain that the efficiency of optimum free fatty acid subtraction could reach 68.75% (bentonite) and 62.50% (zeolite) which much higher than alkaline neutralization by activated bentonite adsorbent (31.28%) and diatomite soil (43.36%). By means of isotherm model obtain that involving mechanism is physical adsorption process by 15.6141 kJ/mole energy (bentonite) and 15.7567 kJ/mole (zeolite), working force is induced dipole-dipole which follow second order kinetics reaction. These results conclude that adsorbent size reduction that enlarges surface area, pore volume and radius could improve significantly the used oil adsorption efficiency for color and free fatty acids parameters.